Pengaruh Kolaborasi Model Pembelajaran Circ Dan Quick On The Draw Terhadap Hasil Belajar IPS pada Siswa Kelas IV SD Inpres Pangalloang Kabupaten Mamuju - Agung Wijaya; Ade Irma Suriani; Syamsuriadi Syamsuriadi; P. Salenda (Journal Innovation In Education, 2023)
This research aims to determine the influence of the collaboration between the Circ and Quick on The Draw learning models on social studies learning outcomes for Class IV students at SD Inpres Pangalloang District. Mamuju. This research uses a quantitative research method. The sampling method in this research uses a saturated sampling technique. The research results obtained the Kolmogorov Smirnov data normality test value which showed that the data was normally distributed. The average score obtained by students on the pre-test score was in the medium category and the average score obtained by students on the post-test score was in the high category with an increase in score of 3.1%. These results show that the collaboration of circ and quick on the draw learning models can improve social studies learning outcomes for fourth grade students at SD Inpres Pangalloang SD Inpres Pangalloang Makassar. The results of the data hypothesis testing analysis obtained a Sig value. (2-tailed) is smaller than the probability value or H0 is rejected and Ha is accepted, which means the data analysis coefficient is positive. So it can be concluded that there is an influence of collaborative learning models and quick on the draw on social studies learning outcomes for fourth grade students at SD Inpres Pangalloang.